Gender Equity, internationalization and quintuple helix: Comparative NLP analysis of university strategies in Japan and Türkiye - Bengü, Elif; Çoymak, Ahmet; Rogler, Andreas; Morozumi, Akiko (Journal of International Students, 2026)
As higher education institutions (HEIs) seek to align with Sustainable Development Goals (SDGs), integrating diversity, equity, and inclusion (DEI) into internationalization strategies has become increasingly central. In this study, we analyze 209 university strategic plans, 86 from Japan (2022–2027) and 123 from Türkiye (2019–2023), to examine how institutional discourse frames gender equity, with a particular focus on SDG 5, gender equality. We identify clear and distinct national patterns using natural language processing (NLP) techniques (e.g., keyword frequency analysis, named entity recognition, and syntactic parsing) and are guided by the quintuple helix model (QHM). Japanese universities tend to emphasize societal engagement and forward-looking commitments through abstract language.